SURVEI TINGKAT KEBUGARAN JASMANI PESERTA EKSTRAKURIKULER DI SMA NEGERI 1 SIDAYU KABUPATEN GRESIK - Muhammad Adam Alif Fahmi; M.E Winarno (Jayabama: Jurnal Peminat Olahraga, 2024)
The purpose of this study was to determine and measure the level of physical fitness of extracurricular participants, which aims to encourage an increase physical fitness activities of students for the body condition becomes healthy and fit so that during the learning process it becomes more optimal. This research is descriptive quantitative with data collection using the TKJI test and the results of the study were analyzed using descriptive statistics with percentages. In this study, after data processing and the results physical fitness test of extracurricular futsal students were obtained at 50%, volleyball at 51%, basketball at 55%, badminton at 53%, passusi at 48%, pencak silat at 54%, scouts at 48%, PMR at 48%, pecinta alam at 50%, theater at 49%, youth scientific at 47%. So the level of physical fitness of extracurricular participants in SMA Negeri 1 Sidayu Gresik with a total population of 159 students gets 50% percent in category less